The speed control of DC motors with Support Vector Machine - Gedikpinar, Mehmet (Wydawnictwo Sigma-N O T Sp Z O O, 2011)
In recent years, the Support Vector Machine (SVM) has been commonly used as both classifier and control due to its advantages, which are sharp distinction surface detection and high accuracy, in the literature. In this study, the speed control of Direct Current (dc) motor system, which has variable parameters for resistance, is performed by using SVM controller. For this reason, the dc motor speed control performance of designed SVM controller is compared with the linear PI controller's. As shown from results, the dc motor speed control performance of designed SVM controller is very high. While the dc motor speed control performance of linear PI controller is degredation, the SVM controller's is robust versus to changes of controller parameter values.
Sterowanie pr?dko?ci? silnika stalopr?dowego z wykorzystaniem sterownika SVM
Keywords: DC motor control; PI controller; intelligent SVM controller; robust control